The Right to the City: conceptual transformations and urban struggles / O Direito à Cidade: transformações conceituais e lutas urbanas - Tavolari, Bianca (Revista Direito e Práxis, 2020)
DOI:10.1590/2179-8966/2020/47788 Abstract This article presents a history of the concept of the right to the city. The reconstruction of the concept’s genesis and development draws on the relation between the history of ideas and the history of social struggles in order to show that the variety of meanings attributed to the right to the city today is decisive to its social and theoretical relevance. Keywords: Right to the city; History of a concept; Henri Lefebvre; Social movements. Resumo Este artigo apresenta uma história do conceito de direito à cidade. A reconstrução da gênese e do desenvolvimento do conceito parte da relação entre a história das ideias e a história das lutas sociais para mostrar que a variedade de sentidos atribuída hoje ao direito à cidade é decisiva para sua importância social e teoria. Palavras-chave: Direito à cidade; História de um conceito; Henri Lefebvre; Movimentos sociais